Glass As A Sustainable Material To Design A Modern Office Building In Seismic Area, A Case of : Banda Aceh, Indonesia - Zia Faizurrahmany El Faridy (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2016)
Glass as a material in building facades is rarely applied in a large scale, especially in design of office buildings, within Aceh province. Since Aceh is located in the area with dynamic earthquake activities, building design in this area required higher degree of concern in relation to better refrain from earthquake movements. Nowadays, glass technology that could withstand the seismic effects while sustaining seismic loads is available. To bring this new technology into design of office buildings in Aceh, the paper aims to measure the suitability and level of acceptance of the technology among Acehnese people by conducting some methods of cost comparison and cost savings. In this regard, a comparison in dead loads of a sample building with conventional cavity walls against that of high performance glazing system in a faÃ§ade of the building was performed. The results indicated that the cost for glass technology are twice higher compared with cavity wall. But in the dead loads part, the glass material are 13.8 times more lighter than cavity wall